The rare translocation t(14;21)(q11;q22) detected in a Moroccan patient with T-cell acute lymphoblastic leukemia. (2019) - Chebihi, Z. Takki; Belkhayat, A.; Chadli, E.; Hessissen, L.; El Khorassani, M.; El Kababri, M.; Kili, A.; Khattab, M.; Bakri, Y.; Dakka, N.
Abstract: Cytogenetic studies of acute lymphoblastic leukemia have been at the forefront of research in the pathogenesis of cancer. The presence of recurring chromosomal abnormalities (either numeral or structural rearrangements) provides immediate clues to the genetic events leading to leukemia and many abnormalities have important prognostic significance. The rare translocation t(14, 21)(q11.2;q22) has been described in pediatric T lineage ALL in only one case so far in 2000. The present study is a case report of an ALL case in which we found a t(14, 21)(q11.2;q22) as a non random chromosomal abnormality among 70 analyzed pediatric ALL cases referred exclusively to BIOLAB Laboratory from the children hospital of Morocco.